การศึกษาการสกัดเพคทินจากกระเจี๊ยบแดงโดยใช้เทคนิคการสกัดด้วยตัวทำละลาย - กรรวี อังศุธรรังสี (คณะวิทยาศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Pectin is a structural polysaccharide which has galacturonic acid as a monomer. Pectin is used as a thickening agent, stabilizer, gelling agent in food such as yam and Jelly. Rosellle is a typical plant in Thailand. Even that roselle contains high amount of pectins and is economical, research papers about roselle as a potential source of pectin are not found much. Thus, this research aimed to study pectin extraction from roselle and to study chemical and physical characteristics of the pectin. In this research, two type of solvent was used which were hydrochloric solution and distilled water with extraction temperature of 30, 60 and 90 ºC and with extraction time of 30, 120 and 240 minutes. The highest production yield of pectin (21.85 ± 0.87) was obtained at temperature of 90 ºC, extraction time of 240 minutes, using Hydrochloric as solvent. The highest production yield of pectin extracted using distilled water (19.91 ± 0.70) is the same condition as hydrochloric. The lowest production yield of pectin (1.05 ± 0.35) was obtained at temperature of 30 ºC, extraction time of 30 minutes, using distilled water as solvent. The highest production yield of pectin extracted using hydrochloric (2.52 ± 0.10) is the same condition as distilled water. The three factors of the experiment which are type of solvent, temperature, extraction time significantly (P<0.05) affected pectin extraction. From L*a*b* color measurement, it was found that L* value is between 21.19 – 43.19 which significantly (p<0.05) affect by temperature and extraction time. A* value was between 10.67 – 30.55 which was significantly (p<0.05) affected by type of solvent, temperature and extraction time. B* value is between -1 – 13.08 and did not show signficant. Moisture content of pectin was between 7.52 – 12.27 which is close to commercial pectin.